PSYCHOLOGICAL FEATURES OF THE MANIFESTATION OF PERFECTIONISM AND ACHIEVEMENT MOTIVATION ACROSS DIFFERENT AGE PERIODS - Marhabo Xayitboyevna Nazaraliyeva (International Journal of Literature and Language Studies, 2026)
Perfectionism and achievement motivation are two of the most extensively studied determinants of goal-directed behavior, yet the way their relationship changes across the adult lifespan remains underexamined outside student samples. This study investigated age-related differences in multidimensional perfectionism (self-oriented, other-oriented, and socially prescribed) and achievement motivation among 1,052 respondents distributed across five age cohorts: early youth (n = 207), adolescence (n = 213), youth (n = 211), maturity (n = 209), and the second stage of maturity (n = 212). Participants completed the Multidimensional Perfectionism Scale (Hewitt & Flett) and T. Ehlers' Achievement Motivation Diagnostic Method. Kruskal-Wallis analyses showed that self-oriented perfectionism (H = 47.05, p < .001), other-oriented perfectionism (H = 70.44, p < .001), and achievement motivation (H = 27.83, p < .001) all differed significantly across age periods, generally increasing from early youth into youth and maturity, whereas socially prescribed perfectionism showed no significant age-related variation (H = 2.48, p = .649). These results indicate that self-directed and other-directed perfectionistic strivings develop alongside achievement motivation across early and middle adulthood, while perfectionism rooted in perceived external demand follows an independent, comparatively stable course. The findings are discussed in relation to contemporary models of motivational development and their implications for educational and occupational counselling.